Wild Dogs: past and present - Halls, Kelly Milner (Plain City, OH Darby Creek Publishing, 2005)
Not all dogs are the playful pets we pamper; being worshipped to being feared as a ravaging monster. What is fiction and what is fact about these furry animals?
5 - 9
Keywords: Wild dogs; Dog family (Mammals).